TEACHERS' PERCEPTIONS ON THE USE OF APPRECIATION AS A COMMUNICATION STRATEGY IN GIVING FEEDBACK - Acep Haryudin; Syihabuddin Syihabuddin (IKIP Siliwangi, 2023)
This study was to find out the teacher's perception of the use of appreciation as feedback in learning, pattern of appreciation and the student's response. The research method used qualitative with questionnaires instruments, 79 teachers and 30 students respondents. The results and findings are the 98.7% teacher knew about appreciation, 100 % importance of giving appreciation, 98.7% the necessity giving appreciation, 100% giving appreciation can increase student motivation, the teacher 96.2% gave appreciation to students who active or doing exercises, 94.9% gives appreciation to students who do exercises even the results are inaccurate, 98.7% giving appreciation can encourage students to achieve, 96.2% giving appreciation related to student learning achievements, 67.1% giving appreciation too often can cause trust inflation in teachers, 79.7% giving appreciation related to teacher personality, 91% student at all levels of education require teachers’ appreciation, 58.2% teachers believe that all teachers always give appreciation. Forms of appreciation carried out by the teacher verbal 15.2%, Written 2.5%, Thumbs Up 0%, verbal / thumbs up 38%, verbal and applause 27.8%, verbal and gift something 16.5%, gifts something 0%. Student responses to appreciation were 60% for verbal and thumbs-up gestures, 35% verbal and written. 5% apreciation with gift.